Nitrate assimilation in chicory roots (Cichorium intybus L.) which acquire radial growth - Druart, N (Journal of experimental botany, 2000)
Nitrate assimilation was analysed in chicory plants (Cichorium intybus L. cv. Turbo) during the early vegetative growth. Nitrate reductase (NR, EC 1.6.6.1) activity (NRA) was measured in roots and leaves at different developmental stages. During phase I, which corresponds to the structural growth (21-42 DAS), nitrate reduction mainly occurred in the roots. At the onset of the tuber formation (phase II), which is characterized by the formation of a cambium inducing a radial growth (42-63 DAS), NRA rapidly decreased in roots and developed in leaves. A tight correlation was found between the nitrate content, the amino acid level and NRA in roots and leaves. Northern blot and ELISA analysis showed that both levels of NR mRNA and NR protein were not modified during the time-course of the experiment suggesting that modification of nitrate assimilation was not controlled at a transcriptional level. In vitro NRA assayed in presence of either Mg2+ ions or EDTA showed that NR was influenced at least in part by a reversible phosphorylation/dephosphorylation reaction. Okadaic acid, a serine-threonine protein phosphatases inhibitor, strongly decreased NRA. Conversely, staurosporine, a serine-threonine protein kinases inhibitor, did not significantly change NRA in roots or leaves. Therefore, NRA was regulated at a post-translational level during the early vegetative growth by modifying the phosphorylation balance of the NR protein in chicory